#MeToo and testimonial injustice: An investigation of moral and conceptual knowledge - Hänel, Hilkje C (Philosophy & Social Criticism, 2022)
Two decades ago, Tarana Burke started using the phrase ‘me too’ to release victims of sexual abuse and rape from their shame and to empower girls from minority communities. In 2017, actress Alyssa Milano made the hashtag #MeToo go viral. This article’s concern is with the role of testimonial practices in the context of sexual violence. While many feminists have claimed that the word of those who claim to being sexually violated by others (should) have political and/or epistemic priority, others have failed to recognize the harm and injury of instances of sexual violence that are not yet acknowledged as such and failed to listen to victims from marginalized social groups. In fact, some feminists have attacked #MeToo for mingling accounts of ‘proper’ sexual violence and accounts that are not ‘proper’ experiences of sexual violence. My aim in this article is to show why this critique is problematic and find a philosophically fruitful way to understand the #MeToo-movement as a movement that strives for moral and conceptual progress.
Keywords: #metoo; approches et analyses; cours; cycles supérieurs; discipline; fem9000; justice sociale; patriarcat; philosophie; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; violences sexuelles

Relational Knowing and Epistemic Injustice: Toward a Theory of Willful Hermeneutical Ignorance - Pohlhaus, Gaile (Hypatia, 2012)
I distinguish between two senses in which feminists have argued that the knower is social: 1. situated or socially positioned and 2. interdependent. I argue that these two aspects of the knower work in cooperation with each other in a way that can produce willful hermeneutical ignorance, a type of epistemic injustice absent from Miranda Fricker's Epistemic Injustice. Analyzing the limitations of Fricker's analysis of the trial of Tom Robinson in Harper Lee's To Kill a Mockingbird with attention to the way in which situatedness and interdependence work in tandem, I develop an understanding of willful hermeneutical ignorance, which occurs when dominantly situated knowers refuse to acknowledge epistemic tools developed from the experienced world of those situated marginally. Such refusals allow dominantly situated knowers to misunderstand, misinterpret, and/or ignore whole parts of the world.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; histoire et politique; ignorance herméneutique; injustices herméneutiques; injustices épistémiques; justice sociale; patriarcat; philosophie; privilèges; racisme; sciences humaines; systèmes d'oppressions; thématiques; éthique